Cointegration and rolling window cointegration analysis of a selected group of stock market indices - Buzzi, Sergio Martín (2015)
Fil: Buzzi, Sergio Martín. Universidad Nacional de Córdoba. Facultad de Ciencias Económicas. Departamento de Estadística y Matemática; Argentina.